High‐accuracy absolute positioning for the stationary planetary rover by integrating the star sensor and inclinometer. Issue 6 (18th February 2020) - Zhan, Yinhu; Zheng, Yong; Li, Chonghui; Wang, Ruopu; Zhu, Yongxing; Chen, Zhanglei
Abstract: In this paper, we introduce a novel method for the high‐accuracy absolute position determination for planetary rovers using the star sensor and inclinometer. We describe the star sensor and inclinometer model and the alignment method for the two sensors. We deduce the compensation algorithm for the atmosphere refraction correction error in detail and provide the rover's position solution, which effectively eliminates the tilt correction error. The experimental site and hardware configuration are introduced, and the experimental steps for the one‐time positioning are described. Three field tests on Earth indicate that the accuracy of the one‐time positioning is higher than 40 m (1σ) using 8 star images and relative inclinometer measurements. Multiple positionings in one night can improve the accuracy to approximately 15 m.